(untitled) (Revista Espinhaço, 2020)
The integration of ecological, environmental, and human health indicators is an innovative tool to assess the environmental quality of urban watersheds, from the perspective of the National Water Resources Policy. The city of Belo Horizonte, Minas Gerais estate, located in the upper Rio das Velhas basin, has used watersheds as territories for planning environmental sanitation at the public policies since the late 1990s. This study aimed to integrate water quality and human health indicators in 10 urban watersheds located at the Belo Horizonte Metropolitan Region. We tested the hypothesis that the health of human populations living in urban sub-basins is possibly related to water quality, and that water quality, including biotic integrity of benthic macroinvertebrate communities (richness and relative abundance) is influenced by land use. Physical and chemical parameters of water quality, biological metrics of benthic macroinvertebrate indicators, human health metrics (infant mortality and hospitalization due to childhood diarrhea), and the conditions of land use (vegetation, impervious area and proportion of streams in natural channel) were analyzed through general linear models. The results showed that the increase in cases of hospitalization for childhood diarrhea in the period from 2005 to 2008 were related to water quality (R2 = 0.35; p < 0.05), due to the decrease of dissolved oxygen in the water. The number of benthic macroinvertebrate taxa resistant to pollution varied positively with the proportion of impervious areas and with the proportion of canalization in the river beds (R2 = 0.63; p < 0.01). It was evidenced that the water quality is associated with the occurrence of diseases in the human population and with the disordered land use in the studied watersheds at the upper Rio das Velhas basin. Growing public investments in sanitation (Goal 2030) are urgent for the improvement of human and environmental health, which may bring benefits to the human population in the metropolitan region of Belo Horizonte city.